Measurement of individual social behaviour and perception of fear during the pandemic by COVID-19 in heads of households - Miranda Copaja, Karolaine Melanie (2022)
Objective: To identify the characteristics of social and individual behavior and perception of fear during the COVID-19 pandemic in socially isolated heads of households. Material and methods: Cross-sectional, prospective and analytical observational study. 372 heads of households resident in Tacna city were included, during the year 2020, selected by multistage sampling; foreigners, bystanders, persons in mandatory isolation due to COVID-19 infection were excluded per confirmed case or suspicious contact and persons who did not take basic biosecurity measure. We applied a questionnaire to measure the perception of social behavior and fear in the home with informed consent. Descriptive and analytical statistics with logistic regression were used to determine strength of association with multivariate analysis. Results: The heads of families were characterized by having ages between 40 and 49 (37.6 %), cohabiting (65.1 %), complete high school (51.1 %). 8.3 % had contact with suspected family members with COVID-19 under the same roof, 34.9 % with close family members. Consider the risk of developing COVID-19 (43.5 %). Regarding social behavior, 89.5 % adopt buying respiratory masks; 81.7 % purchase alcohol; only 39 % adopt hand washing. 54.6 % had partial insulation, 32.8 % preferred not to have an opinion and only 12.7 % had permanent total insulation. Conclusion: There are significant differences according to age and condition of contact with coworkers associated with fear. Social behavior was statistically different according to age, the environment of risk is mainly by co-workers.